Metastases of the appendicular skeleton: an orthopaedic update. Issue 3 (June 2021) - Simpson, Jonathan; Kumar, Amit
Abstract: Metastatic bone disease is a common sequela of malignancy and can lead to significant morbidity on patients. Systemic medical therapies and oncology surgery have greatly enhanced cancer survival rates over recent decades. Orthopaedic surgeons occupy a key position within the multidisciplinary team and coordinate surgical care for bone metastases where appropriate. This review describes the investigations for, and management of, patients with metastases to the appendicular skeleton. National guidelines exist to help orthopaedic clinicians and departments optimize patient care and outcomes. We outline and illustrate the freely available OPTIModel app from the Netherlands, which is an innovative, straightforward and useful tool for prognostic evaluation and suggestion of loco-regional treatment options for patients with symptomatic long bone metastases.